Cephalocteinae Mulsant et Rey, 1866 (Hemiptera, Heteroptera), a subfamily of Cydnidae new for the Italian fauna: first record of Cephalocteus scarabaeoides (Fabricius, 1807) from Sardinia - Fancello, Luca; Cillo, Davide; Bazzato, Erika (Zootaxa, 2016)
Cephalocteus scarabaeoides is recorded from the south-western coast of Sardinia, in sandy habitat (marine dunes near the beach), for the first time. The species and the subfamily are new for the Italian fauna.